The First Smart Pill: Digital Revolution or Last Gasp? - Swartz, Anna K. (Kennedy Institute of Ethics journal, 2023)
Abilify MyCite was granted regulatory approval in 2017, becoming the world’s first "smart pill" that could digitally track whether patients had taken their medication. The new technology was introduced as one that had gained the support of patients and ethicists alike, and could contribute to solving the widespread and costly problem of patient nonadherence. Here, we offer an in-depth exploration of this narrative, through an examination of the origins and development of Abilify, the drug that would later become MyCite. This history illuminates how an antipsychotic can become a top-selling drug and maintain its blockbuster status for more than a decade. It also provides a detailed case study for how knowledge is constructed within the logic of biomedical capitalism, providing impetus to reexamine claims regarding how MyCite addresses patient nonadherence, engenders patient support, and is ethicist-approved.